2017
DOI: 10.1002/ccd.27243
|View full text |Cite
|
Sign up to set email alerts
|

Visual estimation versus different quantitative coronary angiography methods to assess lesion severity in bifurcation lesions

Abstract: Our study showed that bifurcation lesion complexity was significantly affected when more advanced bifurcation QCA software were used. "True" bifurcation lesion rate was 100% on visual estimation, but as low as 13% when analyzed with dedicated bifurcation QCA software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
(50 reference statements)
1
6
0
Order By: Relevance
“…Grundeken et al's data are consistent with the large body of work demonstrating that simple QCA only marginally improves the predictive value of visual assessment including bifurcations. If 2D and 3D bifurcation QCA is eventually validated by FFR in larger studies, (which seems supremely challenging, especially given anatomical/functional mismatch of the varying myocardial bed sizes), then it may be helpful for operators where bifurcation FFR will not or cannot be performed.…”
Section: Limitationssupporting
confidence: 62%
See 2 more Smart Citations
“…Grundeken et al's data are consistent with the large body of work demonstrating that simple QCA only marginally improves the predictive value of visual assessment including bifurcations. If 2D and 3D bifurcation QCA is eventually validated by FFR in larger studies, (which seems supremely challenging, especially given anatomical/functional mismatch of the varying myocardial bed sizes), then it may be helpful for operators where bifurcation FFR will not or cannot be performed.…”
Section: Limitationssupporting
confidence: 62%
“…A limitation of the study by Grundeken et al was the lack of a true anatomic or more importantly functional standard for a bifurcation lesion. As a result, although the number of significant appearing lesions became less severe with more intense QCA methodology, there is no validation with FFR assessment to determine whether 3D QCA reduced false‐positives, or increased false‐negatives.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Medina classification method was used for description of lesion classification in this study. 6 The total kissing balloon diameter was defined as the sum of the diameters of kissing balloons during the operation of the two-stent technology. The proximal optimization technique was defined as use of a short balloon with a larger diameter to dilate the proximal main branch of the bifurcation lesion.…”
Section: Methodsmentioning
confidence: 99%
“…been well covered elsewhere. 6,[12][13][14] The results of the Clinical Outcomes Utilizing Revascularization And Aggressive Drug Evaluation (COURAGE) trial indicated that revascularisation did not reduce the risk of major cardiovascular and cerebral adverse events (MACCE) in stable patients. 15 The Fractional Flow Reserve Versus Angiography For Multivessel Evaluation (FAME) trials highlighted the need for an objective measurement of the significance of high-grade stenoses in terms of their functional relevance prior to intervention.…”
Section: Imagingmentioning
confidence: 99%